(1272) Urbanization and development Some observation and speculations التمدن والتنمية: بعض الملاحظات والتأملات - Elahwal, Abdel Karim A. (The Institute Of National Planning., 2018)
The urbanization process, known to be intimately associated with economic development, deserves attention if we are understand the recent and future mechanizes of change in developing areas. a discussion on the subject can be found in the literature.This literature, however, points to urban developments in the urbanization and economic growth can beat be studied.